2022
DOI: 10.3390/plants11233396
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bacteria of the Genus Pseudomonas on Leguminous Plants and Their Joint Application for Bioremediation of Oil Contaminated Soils

Abstract: The modern approach to the creation of biological products to stimulate plant growth is based on the study of specific inter-bacterial interactions. This study describes the impact that the introduction of strains of the genus Pseudomonas has on annual and perennial leguminous plants and the ecosystem of the leguminous plant—the indigenous microbial community. The objects of research under the conditions of vegetation experiments were plants of field peas (Pisum sativum L.), white lupine (Lupinus albus L.), ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
0
4
0
1
Order By: Relevance
“…Among sugarcane's endophyte compositions, Pseudomonadota dominated the sugarcane tissues. Pseudomonadota contains a wide range of bacteria with growth-promoting effects on plants, and they usually produce phytohormones, solubilise minerals, fix nitrogen and control plant diseases (25,26). In the present study, we found that the average relative abundance of Pseudomonadota isolated from the leaves of S. robustum and S. officinarum reached 97.9% and 98.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Among sugarcane's endophyte compositions, Pseudomonadota dominated the sugarcane tissues. Pseudomonadota contains a wide range of bacteria with growth-promoting effects on plants, and they usually produce phytohormones, solubilise minerals, fix nitrogen and control plant diseases (25,26). In the present study, we found that the average relative abundance of Pseudomonadota isolated from the leaves of S. robustum and S. officinarum reached 97.9% and 98.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of Pseudomonas sp. to enhance plant growth has been attributed to various mechanisms, such as phytohormone production, nutrient solubilization, HCN, siderophore secretion, and biocontrol activity [28]. Pseudomonas koreensis is a species whose representatives are repeatedly mentioned in relation to the possibility of nitrogen fixation and phytohormone production [29], as well as phosphate solubilization, ammonium, and siderophore production [30].…”
Section: Discussionmentioning
confidence: 99%
“…Even though the in vitro germination tests with each of the consortium strains did not show an evident improvement in the germination rate (data not shown), the combined effect of these bacteria caused an improvement in the soil structure, which may better retain the moisture, as well as a reduction in the pH of the soil, which could explain the improvement in germination. In addition, despite not having much information about plant growth-promotion in these species, some of the strains included in the consortium, such as Pseudomonas koreensis , Paenibacillus lautus , and Paenarthrobacter nitroguajacolicus , have been described as growth promoters in other legumes, which could explain the improvement in development in both microcosm conditions [ 86 , 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%